The shaft Brezno pod Velbom - Gabrovšek, Franci (Acta carsologica, 1997)
Kanin mountain in western Julian Alps, Slovenia, is one of the most promising caving areas. On two high karstic plateau many very deep caves have been explored, three of them beyond 1000 m. Brezno pod Velbom, which is now 850 m deep, was found in 1989. It is the 501 meters deep entrance shaft, that makes the cave especialy interesting. It is the world's second deepest vertical, after the shaft Vrtiglavica, which is a single 643 meters deep shaft. Both entrances lie not more than 2 km apart.
Keywords: Brezno pod Velbom; Kanin; kraška brezna; kraške jame; List of caves in Slovenia; Slovenia; Slovenija; speleologija